A single-core fiber Mach-Zehnder interferometric comb filter - Mahdi, Mohd Adzir; Islam, Md. Shafiqul; Ismail, Alyani; Hitam, Salasiah; Abu Bakar, Muhammad Hafiz (2012)
The present invention provides a single-core fiber Mach-Zehnder interferometric comb filter, wherein the filter includes (a) a single-core polarization maintaining fiber (PMF) that consists of two PMF lengths L1 and L2 which are spliced at an angle of approximately 900 to each other about their principle axes wherein a section of the PMF is spliced between two single mode fibers (SMFs) at different angle and a section of PMF is formed of two segments of PMF (PMF1 and PMF2) and the segments (PMF1 and PMF2) are spliced at approximately 900 of their principle axis to each other and wherein the segment PMF1 is spliced with SMF at approximately 45o and the other end of PMF2 is spliced with SMF at 0o with respect to the birefringence axis of the PMF, (b) a half wave plate (HWP) which is used to rotate a birefringence axis at desire value, (c) a quarter wave plate (QWP) which is used for wavelength shifting and (d) a polarization controller (PC) is inserted in-line with the SMF section.